SEMINAR PENGENDALIAN PENCEMARAN DAN PENYEBARAN AIR LINDI DARI REMBESAN KOLAM LINDI TPA SUMOMPO MANADO - Riogilang, Hendra (MEDIA MATRASAIN, 2021)
Reports and complaints from the community around the Sumompo TPA area stated that there had been contamination of groundwater around the Sumompo TPA area. Pollution was found in resident dug wells and waterways suspected of seepage or leaks from the leachate pond facility at the Sumompo TPA. The water is black in color and has a foul smell, so it cannot be consumed and utilized by residents. The Unsrat service team through PKM program activities took the initiative to conduct a scientific study to find out to what extent the concentration of pollution occurred and how far the spread of leachate in ground water was. Next find a solution to control the pollution that occurs. Clarification of public information and the results of scientific studies regarding pollution in the field are disseminated to the government and residents around the Sumompo TPA location. After the seminar, it is hoped that the local community and the management of the Sumompo TPA will understand the pollution that has occurred and make efforts to prevent and treat leachate leaks. So that the ground water around the Sumompo TPA can return to clean and no longer polluted.